Peran Green Wakaf sebagai Instrumen Keuangan Sosial Islam dalam Mendukung SDGs - Nur Lailatul Inayah; Tri Lestari; Mohammad Soleh (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to examine the role of green waqf as an Islamic social finance instrument in supporting the achievement of the Sustainable Development Goals (SDGs). The research method used is a qualitative one with a literature review approach through searching for journal articles, academic books, and relevant scientific documents. The results of the study indicate that green waqf is a productive waqf innovation that focuses on financing environmentally friendly activities and contributes to the achievement of the SDGs, particularly poverty alleviation, clean energy, climate change mitigation, and ecosystem preservation. However, the implementation of green waqf still faces challenges in the form of limited literacy, institutional governance, and nazhir capacity. Therefore, it is necessary to organize and professionalize waqf management so that the role of environmentally friendly waqf can be optimized Keywords: green waqf, Islamic social finance, SDGs, maqasid al-shariah